AB0520 Tocilizumab in rheumatoid arthritis – one year interim analysis of the non-interventional ichiban study. (23rd January 2014) - Specker, C.; Kaufmann, J.; Vollmer, M.A.; Kellner, H.; Bohl-Bühler, M.; Aringer, M.; Alberding, A.; Schwenke, H.; Kühne, C.; Lüthke, K.; Tony, H.P.; Zinke, S.; et al.
Abstract : Background: The ICHIBAN study collects clinical routine data to evaluate the efficacy and safety of tocilizumab (TCZ) in pat. with rheumatoid arthritis (RA) over a period of 2 years. Methods: The start of this prospective, non-interventional study, being intended to include 4000 pat., was in Feb. 2010. Clinical data of RA pat., their therapies, therapeutic responses, pat. related outcomes and adverse events are collected "on the fly" using an online database with structured web forms. Results: On 18th December 2011 as reference date, baseline data of 1036 pat. were available. In 343 pat. observation period was already at least 52 weeks or discontinuation or change of a treatment was documented. 75.4% of the 1036 pat. were female, the mean age was 56.0 years. Pat. suffered from RA since 10.1 years in mean and the baseline DAS28 was 5.4. 73.3% of the pat. had concomitant diseases. 74.4% were pretreated with TNF-alpha inhibitors, 23.9% exclusively with synthetic DMARDs. In week 52 (LOCF) 31.1% of the pat. (N=97/312) showed a remission of DAS28 (<2, 6). A moderate or good EULAR response was seen in 32.3% or 42.2% of the pat., respectively. The mean number of tender joints decreased from 10.1 to 4.4, the mean number of swollen joints from 7.3 to 2.5. The mean ESR decreased from 35.4 to 13.7 mm/1h and the CRP from 3.3 to 0.8 mg/dl. Data on pat. reported outcomes (PRO) and functional status at week 52 are shown in Tab. 1. In 21.9% of the pat. (N=75/343) treatment was changed during the observational period of 52 weeks. The total TCZ exposition was 910.1 pat. years. 781 adverse events were reported (in 339 of the 1036 pat.; 85.8/100 pat. years). 147 of these events were infections (16.2/100 pat. years). 160 serious adverse events were reported (in 95 pat.; 17.6/100 pat. years), 110 of which included an at least improbable causal relationship with TCZ (12.1/100 pat. years). Conclusions: The results of this "real life study" represent a severely diseased RA population showing significant impairments. The first 343 patients having completed the first observation period of at least one year show clear improvements in all recorded RA parameters. These data confirm the results of previous real life studies with TCZ such as ROUTINE and TAMARA. The safety results correspond to the expectations. Disclosure of Interest: C. Specker Grant/Research support from: Has received honoraria from Chugai for advising in study design and conduction and fees for talks, in summary less than €10.000/year, J. Kaufmann: None Declared, M. Vollmer: None Declared, H. Kellner: None Declared, M. Bohl-Bühler: None Declared, M. Aringer: None Declared, A. Alberding: None Declared, H. Schwenke: None Declared, C. Kühne: None Declared, K. Lüthke: None Declared, H. P. Tony: None Declared, S. Zinke: None Declared, A. Kapelle: None Declared, T. Klopsch: None Declared, P. M. Aries: None Declared, S. Remstedt: None Declared, A. Melzer: None Declared, P. Hellmann: None Declared, S. Türk: None Declared, G. Fliedner: None Declared